PERKEMBANGAN HUKUM PERDATA ISLAM DI INDONESIA (ASPEK PERKAWINAN DAN KEWARISAN ) - Suadi, Amran (Jurnal Yuridis, 2015)
This paper discusses the development of Islamic civil law in Indonesia restricted regarding aspects of marriage and inheritance. Discussion of developments means in Islamic civil law in the reform era, either already in the form of implementation or as ideas. These developments can be seen on various topics of discourse and implementations are carried out in Indonesia as a discussion of children born out of wedlock, the legal registration of marriages , polygamous regulation, wasiah wajibah, replacement in inheritence and other issues regarding Islamic law in marriage and inheritance in Indonesia